PENGARUH SMASH BOOK BERBASIS INKUIRI TERBIMBING TERHADAP MOTIVASI BELAJAR SISWA PADA MATERI LARUTAN PENYANGGA - Herlina Apriani; Fitria Rizkiana (Universitas Lambung Mangkurat, 2018)
Abstract. Learning media is one of the learning process component that can support the achievement of learning goals. Creative learning media can attract students' attention to learning material. This study aims to determine the effect of smash book based guided inquiry to student’s learning motivation on buffer solution material. The sample of this study is students of class XI IPA 1 and XI IPA 2 SMA KORPRI Banjarmasin academic year 2017/2018. This research is quasi-experimental research. The design used in this study is the nonequivalent post-test control group design. The data were collected using an instrument in the form of learning motivation questionnaire. Data were analyzed using Mann Whitney U test assisted by SPSS after homogeneity and normality tests. The results showed that there was effect of smash book based guided inquiry to student’s learning motivation on buffer solution material.Keywords: guided inquiry, learning motivation, smash book